Chicken genetic diversity, improvement strategies and impacts on egg productivity in Ethiopia: a review. Issue 3 (3rd July 2022) - Chebo, Chencha; Betsha, Simret; Melesse, Aberra
SUMMARY: Chicken production is a vital part of livestock production in Ethiopia. Amongst others, it provides economic, cultural and religious benefits. With few intensive chicken farms in and around cities, the major production system is traditional chicken farming that supports more than 85% of producers and sources of major egg and chicken meat supplies. Unimproved local chickens are commonly used which are characterised by low egg production, late-maturing and long brooding behaviour. As a result, various exotic chicken breeds were imported to different parts of the country with an aim to improve egg and meat production. So far, more than 20 exotic chicken breeds were introduced. The crossbreeding strategy had shown a certain extent of positive impact at both smallholder and intensive farming conditions. However, it was criticised for unplanned implementation, uncontrolled and indiscriminate crossbreeding that led to a genetic dilution of local genotype and reduction in performances of improved breeds under extensive systems. Moreover, it has resulted in the erosion of adaptive local genetic resources to various stressful tropical environments. So, many research findings confirm, the unsustainability of crossbreeding attempts under farmer's management conditions and in search for optional strategies. As result, a selective breeding (Horro chicken breed) and synthetic breed (DZ-white) were developed and showed better performance under on-farm and on-research stations. Recently, improved Horro breeds are at their 11th generation of selection, whereas DZ-white synthetic breed is at the 5th generation. In general, chicken breeding in Ethiopia is known for lacking a sustainable breed improvement plan, limited selective breeding on targeted economic traits, a lack of a working breeding policy and evaluation for genetic gains using records. Therefore, the current mass importation of the exotic breeds is harming local genetic diversity; so it should be minimised and adapted crossbreds could be focused, besides Horro selective breeding and adoption of DZ white synthetic breed.